2022
DOI: 10.3389/fpsyt.2022.887700
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Expression of DNA-Methyltransferase and Cannabinoid Receptor mRNAs in Blood Lymphocytes After Acute Cannabis Smoking

Abstract: BackgroundCannabis use is a component risk factor for the manifestation of schizophrenia. The biological effects of cannabis include effects on epigenetic systems, immunological parameters, in addition to changes in cannabinoid receptors 1 and 2, that may be associated with this risk. However, there has been limited study of the effects of smoked cannabis on these biological effects in human peripheral blood cells. We analyzed the effects of two concentrations of tetrahydrocannabinol (THC) vs. placebo in lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The clinical use of drugs containing cannabis derivatives for the treatment of different CNS diseases is supported by several studies [2]; CBD, and cannabinoids in general, could exert analgesic and anti-inflammatory effects in several pain-related diseases [2][3][4]. The ability of CBD to trigger positive effects in several diseases was widely investigated and described [1,5,6,10,30], but, recently, it was also shown that cannabis smoking is able to induce changes in the expression of DNA-methyltransferase in lymphocytes, even if these results are not clearly related to specific clinical relevance [31].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical use of drugs containing cannabis derivatives for the treatment of different CNS diseases is supported by several studies [2]; CBD, and cannabinoids in general, could exert analgesic and anti-inflammatory effects in several pain-related diseases [2][3][4]. The ability of CBD to trigger positive effects in several diseases was widely investigated and described [1,5,6,10,30], but, recently, it was also shown that cannabis smoking is able to induce changes in the expression of DNA-methyltransferase in lymphocytes, even if these results are not clearly related to specific clinical relevance [31].…”
Section: Discussionmentioning
confidence: 99%
“…Although our results showed no changes in DNMT3a or DNMT3b expression, Vassall et al [ 103 ] found decreased DNMT3a , while Fuchs Weizman et al [ 57 ] found reduced DNMT3b expression, both in vivo and confirmed in vitro, in THC exposed human GCs. Smith et al [ 104 ] also found TET3 upregulated in blood lymphocytes paired with detected THC levels, following acute cannabis smoking. These varied results are likely from different study designs, such as exposure route (in vitro vs inhalation), time of exposure, different models and the effects of other cannabis components, such as CBD.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to Cnr1, Cnr2 gene regulation by DNA methylation mechanisms has been less studied. However, THC consumption has been shown to enhance CB 2 expression in human blood lymphocytes via changes in DNMT and TET mRNAs [ 89 ]. Although no direct link between these events was established, these observations may suggest that increased DNMT-methylating enzymes are associated with some of the pathophysiological processes in schizophrenia and, therefore, should be one of the potential mechanisms linking cannabis use as a trigger for schizophrenia in vulnerable individuals.…”
Section: Role Of Dna Methylation: Cannabinoid Receptorsmentioning
confidence: 99%